Factors affecting customer decisions in using the GoFood application in Indonesia - Cuanda, Jonathan; Subali, Stefanus (Southeast Asian Journal of Service Management, 2026)
The rapid development of online food delivery services necessitates a more in-depth study to analyze the factors that influence customer decisions in using the GoFood application in Indonesia. The main objective of this study is to examine the influence of perceived usefulness, ease of use, enjoyment, trust, and social influence on attitude and behavioral intention, as well as the influence of attitude on the behavioral intention of GoFood users. The respondents in this study were 303 GoFood users in Indonesia. The analysis technique used was Structural Equation Modeling (SEM), which was analyzed using the AMOS 23 application. The results showed that perceived usefulness, ease of use, enjoyment, trust, and social influence had a significant effect on attitude. In addition, perceived usefulness, trust, social influence, and attitude also had a significant effect on behavioral intention in the use of GoFood, except for the direct effect of enjoyment on behavioral intention, which was not significant.